2022
DOI: 10.1038/s41598-022-15713-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of joint interactions with humans and social interactions with conspecifics on the risk of zooanthroponotic outbreaks among wildlife populations

Abstract: Pandemics caused by pathogens that originate in wildlife highlight the importance of understanding the behavioral ecology of disease outbreaks at human–wildlife interfaces. Specifically, the relative effects of human–wildlife and wildlife-wildlife interactions on disease outbreaks among wildlife populations in urban and peri-urban environments remain unclear. We used social network analysis and epidemiological Susceptible-Infected-Recovered models to simulate zooanthroponotic outbreaks, through wild animals’ j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Most members of the Streptococcus and Sarcina are potential pathogenic bacteria in humans and animals (Wyder et al, 2011;Tintara et al, 2019). The prediction results of wide-scale phenotypic properties KEGG pathways also support that the captive breeding may cause the increase of potential pathogens in gut of these macaques (Amato et al, 2016;Balasubramaniam et al, 2022). In particular, the loss of diversity in gut microbiome will increase the risk of opportunistic infection (Arrieta et al, 2014;Malard et al, 2021).…”
Section: Discussionmentioning
confidence: 72%
“…Most members of the Streptococcus and Sarcina are potential pathogenic bacteria in humans and animals (Wyder et al, 2011;Tintara et al, 2019). The prediction results of wide-scale phenotypic properties KEGG pathways also support that the captive breeding may cause the increase of potential pathogens in gut of these macaques (Amato et al, 2016;Balasubramaniam et al, 2022). In particular, the loss of diversity in gut microbiome will increase the risk of opportunistic infection (Arrieta et al, 2014;Malard et al, 2021).…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, social proximity EC and multilayer affiliative centrality were better predictors of participation compared to grooming EC. Greater proximity to conspecifics might encourage animals to take more risks, for example jointly interact with humans [137] or participate in IGC (this study, [6,78]). Moreover, coalitionary support ties within groups may better ‘prime’ animals to participate in IGC, given the links between participation and intragroup cooperation and conflict resolution [55].…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation is that in macaques, and in other group-living animals that show similar organizations, males spend more time in the periphery and tend to disperse away from their natal groups, and may therefore face greater intergroup encounters than females [102,154,155] Moreover, limited research on wildlife populations in anthropogenically-impacted environments has to-date revealed that males more so than females tend to engage more frequently with humans (e.g. African elephants, Loxodonta africana [156]; macaques: [91,119] and/or jointly aggregate around anthropogenic factors (macaques [137]). Thus, participation by males in IGC might be an artefact of participation in human-wildlife interactions over food, or vice versa, due to which, males may be more likely to encounter members of other groups than females.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism that determines the emergence of new VOCs, such as Omicron [26,27], remains unknown, it is clear that the virus is transmitted via infected individuals and replicates within their organs, giving rise to mutations in the SARS-CoV-2 genome. Only a few mutations can enhance the virus's functions and its degree of infectivity (i.e., the capacity of the virus to enter human host cells), transmissibility (the capacity of the virus to move from one host to another) and immune escape, giving rise to VOCs.…”
Section: New Vocs: What To Expect and What To Domentioning
confidence: 99%